PENGARUH KEEFEKTIFAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH KEJURUAN NEGERI 31 (SMKN 31) JAKARTA-PUSAT - Dewi Nurmalasari (Fakultas Ekonomi Universitas Negeri Jakarta, 2015)
Abstract The objectives of this research was identify the effect of leadership effectiveness to teacher performance. The design of this research applies survey method. The responden are teacher at thirty one vocational high school (SMKN 31) with 55 teacher. Data analysis condition used normality test using skewness-kurtosis value used to know how normal data distribution in each variable represent by gradient. The result of this research conclude that there is positive effect leadership effectiveness to teacher performance with coefficient correlation rX1Y1 = 0.933 determination correlation 0.869 which showed variance 86.9 %. From this research conclude that leadership effectiveness giving significant contribution on employee performance. The result showed that variable can be good predictor to employee performance. Keywords: headmaster leadership effectiveness, teachers performance